Avacchedakatāniruktiḥ: dīdhitigādādharībhyāṁ sahitā = The Avacchedakatānirukti (of the Dīdhiti and Gādādharī) : with the Subodhā commentary - Gadādhara Bhaṭṭācārya (Regards sur l'Asie du Sud, 2017)
On neo-Nyaya school in Hindu philosophy